Current evidence of the economic value of One Health initiatives: A systematic literature review - Auplish, Aashima; Raj, Eleanor; Booijink, Yoeri; de Balogh, Katinka; Peyre, Marisa; Taylor, Katrin; Sumption, Keith; Häsler, Barbara (One health, 2024)
Funding and financing for One Health initiatives at country level remain challenging as investments commonly require demonstrated evidence of economic value or returns. The objectives of this review were to i) identify, critically analyse and summarise quantitative evidence of the net economic value of One Health initiatives; ii) document methodologies commonly used in the scientific literature; and iii) describe common challenges and any evidence gaps. Scientific databases were searched for published literature following the PRISMA guidelines and an online survey and workshop with subject matter experts were used to identify relevant grey literature. Studies were included if they reported on quantitative costs and benefits (monetary and non-monetary) and were measured across at least two sectors. Relevant publications were analysed and plotted against the six action tracks of the Quadripartite One Health Joint Plan of Action to help classify the initiatives. Ninety-seven studies were included. Eighty studies involved only two sectors and 78 reported a positive economic value or return. Of those studies that reported a positive return, 49 did not compare with a sectoral counterfactual, 28 studies demonstrated an added value of using a cross-sectoral approach, and 6 studies demonstrated an added value of One Health communication, collaboration, coordination, and capacity building. Included studies most frequently related to endemic zoonotic, neglected tropical and vector-borne diseases, followed by health of the environment and food safety. However, diversity in economic analysis methodology between studies included resulted in difficulty to compare or combine findings. While there is a growing body of evidence of the value of One Health initiatives, a substantial part of the evidence still focuses on “traditional” One Health topics, particularly zoonoses. Developing a standardised and practical approach for One Health economic evaluation will facilitate assessment of the added value and gather evidence for One Health to be invested in and endorsed by multiple sectors.